Approche lexico-cognitive des "mots en kn-’" du vocabulaire anglais - Line Argoud (Anglophonia)
In the English lexicon, I explore the class of lexical items beginning with kn- (phonologically/n/in contemporary English). The overall objective is to show that the semiological invariance of this henristically-formed class corresponds to a notional invariance within a particular subset of ‘kn- words’. I claim that kn- is the surface mark of a submorphemic invariance whose source may be traced back to the conceptualization of body joints, emblematically represented by the ‘knees’.